OPTIMALISASI PELAKSANAAN PEMBELAJARAN BINA WICARA UNTUK MENDUKUNG KEMAMPUAN KOMUNIKASI ANAK TUNARUNGU - Hermanto Hermanto (MAJALAH ILMIAH PEMBELAJARAN, 2008)
Communication ability of deaf children has not reached maximum result yet generally as their parent’shope although getting the instructional of bina wicara in school. The maximum unreachable ability ofthese deaf-children’s communication is influenced by some factors namely The main factor,surely,is onthe children condition themshelves namely the limitation of vocabulary, low control ability of soundperception and rythm, immature of articulation ability, and low mastering in total communication.Second, the teacher’s low ability and skill in bina wicara instructional. Third, lack of supporting facilitiesof bina wicara instructional. Fourth, lack of cooperation among teachers in supporting communicationability of deaf children. From some factors that obstacle the communication ability of deaf-children,so, itmust be togather-awareness and to be solved soon. Because of that, the optimalization of bina wacarainstructional implementation becomes a key to support the result and communication ability of deafchildren.